Isolation And Identification Of Certain Bacteria Of Public Health Importance From Market Beef - Binsy Mathew (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 2001)
In the present investigation, 100 retail beef samples were collected from retail shops located at East Fort (EF), West Fort (WF) Sakthanthampuran Market (SM) and Mannuthy (MN) areas. From each area 25 samples were collected and were brought to the laboratory in a thermocool container. All samples were subjected to estimate Total Viable Count (TVC), Coliforms count (CC), Faecal streptococcal count (FSC) and Escherichia coli count (ECC) and also for the isolation and identification of Escherichia coli, salmonellae Staphylococcus aureus, and Listeria monocytogenes. The overall mean total viable count of the samples belonging to four areas was 6.66 ± 0.08 10glOcfu/g. The mean total viable count of EF, WF, MN and SM areas was 6.61 ± 0.15, 6.68 ± 0.17, 6.49 ± 0.15 and 6.84 ± 0.1910glOcfu/g respectively. One, 13 and 23 per cent had counts at the level of 109, 108 and 107 cfu/g respectively and 46 per cent and 17 per cent of the samples had counts at the level of 106 and 105 cfu/g. The overall mean coliforms count was 2.73 ± 0.09 log.scfu/ g. The mean coliforms counts obtained from the samples of EF, WF, MN and SM areas were 2.78 ± 0.16, 2.84 ± 0.14, 2.62 ± 0.22 and 2.70 ± 0.18 10glOcfu/g respectively. The percentage of sample that had counts at the level of 104, 103 and 102 were two, 46 and 45 respectively. The overall mean Escherichia coli count was 3.56 ± 0.17 10glOcfu/g. The mean Escherichia coli counts of EF, WF, MN and SM areas were 3.11 ± 0.38,4.00 ± 0.27; 3.52 ± 0.37 and 3.60 ± 0.34 10glOcfu/g respectively.